Differences in ground reaction forces during landing between volleyball spikes - Kabacinski, J.; Murawa, M.; Dworak, L. B.; Maczynski, J. (Trends in Sport Sciences, 2017)
The peak values of the vertical ground reaction force in the landing phase of attacks suggest a external loads of volleyball player. The high dynamic loads during landing in volleyball jumps may cause lower extremity injuries. Aim of Study. The main purpose of this study was to compare the impact forces between three different volleyball attack techniques. Material and Methods. Twelve female volleyball players (mean±standard deviation: age 22.3±4.2 years, body height 183.0±8.7 cm, body mass 74.4±10.9 kg) participated in the laboratory tests. A force platform was used to measure the ground reaction forces (GRFs) during landing in volleyball spikes. The vertical (v) component of GRF and horizontal (h) components (resultant) of GRFs, buildup index of these forces (vBIF, hBIF) and time to peak GRF (Tv, Th) were analyzed. Results. No significant differences in Tv and Th (from 0.05±0.01 s to 0.06±0.01 s) between the three volleyball jumps were demonstrated (p<0.05). Significant differences in the peak vGRF, hGRF, vBIF and hBIF between the back row attack and front row attack (23.7%, 18.2%, 38.2% and 29.7%, respectively), and between the back row attack and slide attack (21.1%, 27.3%, 28.7% and 26.4%, respectively) were found (p<0.05). The highest values of peak vGRF (3.8±0.3 BW/m), peak hGRF (1.1±0.2 BW·m-1), vBIF (79.4±14.6 BW/m·s) and hBIF (21.2±7.2 BW/m·s) were obtained during landing in the back row attack (p<0.05). Conclusions. The peak vGRF and vBIF during landing in volleyball spikes ranged: from approximately 3 to 4 BW/m (vGRF) and from approximately 50 to 80 BW·m-1·s-1 (vBIF), and were several times higher than hGRF and hBIF. Increased impact forces in spikes indicate higher external loads during landings and a greater risk of lower extremity injuries in female volleyball players.